Stereoselective synthesis and structural elucidation of dicarba peptides. Issue 24 (19th February 2016) - Gleeson, Ellen C.; Wang, Zhen J.; Robinson, Samuel D.; Chhabra, Sandeep; MacRaild, Christopher A.; Jackson, W. Roy; Norton, Raymond S.; Robinson, Andrea J.
Abstract : Preformed Z - and E -diaminosuberic acid residues can be used to synthesise target dicarba peptides. 13 C NMR spectroscopy can be used to assign stereochemistry in dicarba peptides. Abstract : A facile stereoselective synthesis of cis and trans unsaturated dicarba peptides has been established using preformed diaminosuberic acid derivatives as bridging units. In addition, characteristic spectral differences in the 13 C-NMR spectra of the cis - and trans -isomers show that the chemical shift of carbons in the Δ4, 5-diaminosuberic acid residue can be used to assign stereochemistry in unsaturated dicarba peptides formed from ring closing metathesis of linear peptide sequences.